Building Evacuation with Mobile Devices - Merkel, Sabrina (KIT Scientific Publishing, 2014)
The rapidly growing world population and increasingly dense settlements demand ever-larger and more complex buildings from today's engineers. In comparison to this technological progress, a building's equipment for emergency evacuation has been hardly developed further. This work presents a concept for a building evacuation system based on mobile devices. Furthermore, various algorithms for route planning with mobile devices and for indoor localization of mobile devices are addressed.